Nueva información sobre el Ipequí (Heliornis fulica) en la provincia de Chaco, Argentina - Braslavsky, Oscar; Bodrati, Alejandro; Cockle, Kristina; Avedano Schaller, Mirko (Nuestras Aves, 2005)
Este artículo no cuenta con un resumen.